Elevated Serum Cytokines as Biomarkers for Type 1 Diabetes Mellitus in Diyala Province - Shahrazad Ahmed Khalaf; Hamid K AL-Tameemi; Ali G. Al-Dulimi; Wedyan Yaseen Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
The study aims to examine the levels of cytokines in the serum of individuals with type 1 diabetes mellitus and compare these levels to those of healthy controls. This research aimed to assess the levels of some cytokines that includes IL-4, IL-9, IL-13, IL-35, IL-12, IL-17, IL-21 and IL-33 in Type I diabetes mellitus. In this study, 60 samples were collected from patients and 30 samples from healthy individuals, collected during the period from the of July 2023 to the March 2024.Results of this study showed a significant increase in the concentration of IL-4, IL-9, IL-13, IL-35, IL-12, IL-17, IL-21 and IL-33 in the serum of type 1 diabetes mellitus with the control group there were [10.22±2.065, 73.983±5.117, 35.90±3.343, 3.10±1.612, 19.80±3.433, 20.86±4.010,70.75±8.57, and 398.71±47.157, respectively] than in healthy groups [6.793±0.924, 47.00±5.535, 20.72±2.534, 1.01±10.597, 10.34±2.036, 10.79±1.818, 44.83±7.201 and 277.59±39.451, respectively. The results of the current study showed an imbalance in cytokines production that includes IL 4, IL 9, IL 13, IL 35, IL 12, IL 17, IL 21 and IL 33 in type 1 diabetes mellitus [T1DM] patients. The imbalance between pro- and anti-inflammatory cytokines could contribute to pancreatic β-cell destruction, offering insights for potential biomarkers and future therapies. تهدف هذه الدراسة إلى فحص مستويات السيتوكينات في مصل الأفراد المصابين بداء السكري من النوع الأول ومقارنة هذه المستويات بمستويات الافراد الاصحاء. يهدف هذا البحث إلى تقييم مستويات بعض السيتوكينات التي تشمل انترلوكين-4 , انترلوكين 9 , انترلوكين13 , انترلوكين 35 , انترلوكين 12, انترلوكين 17,انترلوكين 21 وانترلوكين 33 في مرضى السكري من النوع الاول.تم في هذه الدراسة جمع 60 عينة من المرضى و30 عينة من الافراد الاصحاء, تم جمعها خلال الفتره من يوليو 2023 إلى مارس 2024. اظهرت نتائج هذه الدراسة زيادة كبيرة في تركيز انترلوكين-4 , انترلوكين 9 , انترلوكين13 , انترلوكين 35 , انترلوكين 12, انترلوكين 17,انترلوكين 21 وانترلوكين 33 في مرضى السكري من النوع الاول مقارنة بالاصحاء (10.22±2.065, 73.983±5.117, 35.90±3.343, 3.10±1.612, 19.80± 3.433, 20.86± 4.010, 70.75±8.57 و 398.71±47.157 على التوالي مقارنة بالافراد الاصحاء(6.793±0.924, 47.00±5.535, 20.72±2.534, 1.01±10.597, 10.34±2.036, 10.79±1.818, , 44.83±7.201 و277.59±39.451 على التوالي.اظهرت نتائج الدراسة الحالية خلل في انتاج السيتوكينات المدروسة في مرضى السكري من النوع الاول. يمكن أن يساهم خلل التوازن بين السيتوكينات المؤيدة والمضادة للالتهابات في تدمير خلايا بيتا البنكرياسية، مما يوفر رؤى حول المؤشرات الحيوية المحتملة والعلاجات المستقبلية